Collaborative modes with Cultural and Creative Industries and innovation performance: The moderating role of heterogeneous sources of knowledge and absorptive capacity. (April 2020) - Santoro, Gabriele; Bresciani, Stefano; Papa, Armando
Abstract: Organizations can no longer be isolated entities in the current dynamic competitive environment but tend to establish alliances and networks with external parties. Recently, research has suggested that organizations develop collaborative modes with Cultural and Creative Industries (CCIs) to acquire and combine Heterogeneous Sources of Knowledge (HSK) within their organizational environment. Innovation thus becomes increasingly generated by a cross-process involving a diverse set of industries. Nevertheless, few studies have assessed how knowledge from distant industries, such as CCIs, can affect firms' innovation performance. Accordingly, this empirical research on a sample of 187 firms evaluates whether formal and informal collaboration modes with CCIs affect innovation performance. Moreover, it assesses the moderating role of both HSK and absorptive capacity. In particular, it aims to answer the following questions. What are the effects of collaboration modes with CCIs on firms' innovation performance? What are the differences (in terms of effects) between Formal Collaboration Modes (FCMs) and Informal Collaboration Modes (ICMs) with CCIs on firms' innovation performance? Do heterogeneity of knowledge sources and absorptive capacity increase the possibility of benefiting from FCMs and ICMs with CCIs in terms of innovation performance? The results contribute to the theory indicating that HSK are important to benefit from knowledge from CCIs, while absorptive capacity does not fulfil the same role. Highlights: Firms benefit from informal collaboration modes with CCIs. Heterogeneous Sources of Knowledge help in benefiting from formal and informal collaborations with CCIs. Absorptive capacity is not essential in formal and informal collaborative modes.